On Identities and Ethnomedicinal Claims of some Common Botanicals Sold by Vendors in North Maharashtra, India - Patil3*, Y. A. Ahirrao1, Patil M.V.2; D. A. (Journal of Phytology, 2011)
The present paper deals with the botanicals sold by the vendors in Nasik, Dhule Nandurbar Jalgaon and Buldhana districts of North Maharashtra (India). An ethnobotanical survey was carried out since June 2008 and information was obtained through open discussions and interviews with tradipractitioners. Presently, 32 plant species of 29 genera belonging to 24 families are communicated. Of these 26 species are being noted for the first time from Indian region. These are administered in the form of decoction, infusion, paste, oil, ash, juice, powder, extract, slurry or in the form of particular recipes.Â Even they are used raw or sometimes simply warmed.Â In many cases, they use them as a sole drug or occasionally supplemented by other botanicals or substances like lump sugar, honey, oil, cow ghee, cow urine, etc. These are used to combat common diseases such as rheumatism, arthritis, acidity, scabies, wounds, jaundice constipation, diarrhea, dysentery, cough, menstrual complaints, stomach-ache, tooth-ache, ear-ache, paralysis diabetes, piles, impotency, kidney-stone, dropsy, nocturnal emission, goiter, leucorrhoea, abortion, fever etc. The data accrued is assessed by cross-cultural comparisons with other Indian claims to bring out veracity and uniqueness of the claims made. The objective of investigation was to gather and document information on utilization of botanicals by the tradipractitioners in the region. Key words: Ethnomedicine, Vendors, North Maharashtra <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Y. A. Ahirrao et al. On Identities and Ethnomedicinal Claims of some Common Botanicals Sold by Vendors in North Maharashtra, India. J Phytol 2/12 (2010) 09-13.